An Analysis of the Intersection between Urban Entrepreneurship and the Use of Digital Tools - Sanchez, David Leandro Álvarez (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study examines the state of urban entrepreneurship in El Salvador, focusing on its transition to digital environments. Employing a qualitative, phenomenological approach, the research analyzes the lived experiences of 12 entrepreneurs from the eastern region of the country, selected through purposive sampling. Data were collected via semi-structured interviews and participant observation, leading to the identification of key thematic categories: offline–online integration, market reach, technological adaptation, and cultural influence. The findings indicate that social media platforms play a crucial role in expanding market access, reducing operational costs, and re-signifying cultural symbols within commercial practices. Despite these benefits, the persistent digital divide and technological barriers constrain the full transformative potential of digital entrepreneurship. The study concludes that successful integration between physical and virtual commercial domains relies not only on access to digital infrastructure but also on entrepreneurs' capacity to navigate evolving sociocultural dynamics. This research advances the field of commercial cyber-anthropology and provides practical insights for strengthening the local digital economy in developing contexts.